THE KULTUK VOLCANO: SPATIAL-TEMPORAL CHANGE OF MAGMATIC SOURCES AT THE WESTERN TERMINUS OF THE SOUTH BAIKAL BASIN BETWEEN 18 AND 12 MA - S. V. Rasskazov; T. A. Yasnygina; I. S. Chuvashova; E. A. Mikheeva; S. V. Snopkov (Геодинамика и тектонофизика)
The Kultuk volcano erupted at the axial South Baikal basin of the Baikal rift zone (BRZ). Now it exhibits facies of subvolcanic bodies, land-lava eruptions and subaqueous pillow lavas and hyaloclastites. The volcano was controlled by the Obruchev fault that is currently a border of the basin which amplitude of vertical movements is rapidly decreasing in the westward direction. It is found that the Kultuk volcano was active at the beginning and end of the volcanic activity period of the Kamar, Stanovaya, and Bystrinskaya volcanic zones, which took place 18–12 Ma ago. In previous papers, it was assumed that dominant structures in the area under study were major Cenozoic shear displacements along the Main Sayan fault and/or along the Tunka rift valley; however, at the current stage of our study, linear configurations of the volcanic zones do not reveal any of such displacements. Based on analyses of distribution of volcanic rocks in the relief at the western coast of Lake Baikal, distinct vertical crustal movements are revealed; such movements started in the Early Miocene and continue to the present time. It is concluded  that volcanism was controlled by the trans-tensional system of volcanic zones. Sources are identified for the shallow lithospheric mantle melt with the substantial admixture of the low-crust component and deeper asthenospheric mantle melts in the Kamar and Stanovaya volcanic zones; for the Bystrinskaya volcanic zone, only components from the deeper source are revealed. The local shallow mantle magmatism occurred only within the lithosphere extension zone beneath the South Baikal basin. The lithosphere thinning is reflected in the change of activity from the sub-lithospheric to lithospheric sources under the Kamar zone. Rifting of the axial structure is recorded at the root of the Slyudyanka lithospheric block that was subjected to the collision-related Early Paleozoic metamorphism. Geochemical characteristics of the collision-type components were inherited by the Miocene basaltic melts.